Astigmatism research and application of vector method of the last half century: a bibliometric and visualized analysis - Zhang, Jiamei; Xu, Lulu; Shan, Mengyuan; Yuan, Liyun; Dong, Yi; Wang, Yan (Frontiers in Medicine, 2025)
BackgroundAs a common type of refractive error, astigmatism has always been one of the important factors affecting visual quality in clinical practice and it is quite an important public health burden. This study aims to evaluate astigmatism research and the clinical application of the vector method of the past half-century through a broad scientometric analysis, and to explore its reference value for guiding clinical treatment.MethodsThe literature search was conducted on the Web of Science for astigmatic vector studies published from 1965 to August 2024. Retrieved publications were analyzed by the number of annual publications, prolific countries, and researchers, core publications and journals, and the number of citations through descriptive statistics. Collaboration networks and keyword analysis were visualized by VOSviewer and CiteSpace.ResultsOne thousand and fifty-nine publications were included for a visualized analysis. Vector methods help researchers to describe astigmatism specialized, and clinicians are mainly focused on the correction of astigmatism in both corneal and cataract surgery. Journal of Cataract and Refractive Surgery was the core journal for this field. The United States accounts for the largest proportion of publications and Australia had the highest citation ratio. Through the keyword analysis, the network identified 4 major research trends of corneal refractive surgery, penetrating keratoplasty, cataract surgery, and epidemiological surveys of astigmatism. “Photorefractive keratectomy,” “postoperative astigmatism” and “surgery” had significant burst strength and continuous attention to the astigmatism vector analysis.ConclusionVector analysis is the most commonly used method to evaluate astigmatism and could significantly improve the accuracy of astigmatism correction, particularly in areas of refractive and cataract surgery. The application of vector analysis is beneficial in guiding the design of surgical incisions, determining the nomogram, optimizing the surgical protocol, and improving the accuracy of astigmatism correction. Meanwhile, the popularization of vector method will help to improve the accuracy of astigmatism analysis and promote the benign development of public health.